THE USE OF E-TOOLS IN LEARNING ENGLISH BY EFL STUDENTS AT YARMOUK UNIVERSITY - Bassam Al Aroud; Kamariah Yunus (INTERNATIONAL JOURNAL OF EDUCATION, PSYCHOLOGY AND COUNSELLING (IJEPC), 2024)
The objective of this paper was to investigate English as foreign language students at Yarmouk University engagement in using e-learning tools in learning the English language. This study was conducted in Jordan. This mixed-method approach comprised 30 English Language and Literature students in their 1st Year of study selected randomly. This study used a single research instrument that included a 16 items observation checklist. The elicited data were analyzed using textual analysis coding and SPSS, complemented by descriptive statistical analysis of the questionnaire responses. The findings indicated that past experiences relevant influenced EFL Jordanian undergraduate students at Yarmouk University’s use of e-learning tools / MOOCs when learning the English language.